2016
DOI: 10.1021/acs.organomet.6b00346
|View full text |Cite
|
Sign up to set email alerts
|

Strong Electron-Donating Ligands Accelerate the Protodeauration Step in Gold(I)-Catalyzed Reactions: A Quantitative Understanding of the Ligand Effect

Abstract: We have conducted a theoretical exploration of the ligand electronic effect in the protodeauration step of a model gold(I) cyclization reaction, for which experimental data are available. The mechanism of the protodeauration is investigated through a density functional theory (DFT) approach, and the electron-donating power of the ligand is quantified through the charge displacement function (CDF). We find that the frequently encountered assumption in the literature that "strong electron-donating ligands accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 77 publications
5
36
0
Order By: Relevance
“…13 Notably, Roth and Blum 22 observed that the presence of the NHC ligand nearly doubled the rate of proto-deauration compared to the analogous triphenylphosphine complex. In line with this experimental study, theoritical studies by Belanzoni and colleagues 23 showed that electron-donating ligands reduce the electrostatic component of the Au−C bond undergoing proto-deauration, which in turn reduces the activation barrier for this process. Given that NHCs are some of the most strongly electron-donating ancillary ligands, 24 the observed high activity of Cat-1 compared to Cat-0 is reasonable.…”
Section: Journal Of the American Chemical Societysupporting
confidence: 78%
“…13 Notably, Roth and Blum 22 observed that the presence of the NHC ligand nearly doubled the rate of proto-deauration compared to the analogous triphenylphosphine complex. In line with this experimental study, theoritical studies by Belanzoni and colleagues 23 showed that electron-donating ligands reduce the electrostatic component of the Au−C bond undergoing proto-deauration, which in turn reduces the activation barrier for this process. Given that NHCs are some of the most strongly electron-donating ancillary ligands, 24 the observed high activity of Cat-1 compared to Cat-0 is reasonable.…”
Section: Journal Of the American Chemical Societysupporting
confidence: 78%
“…The CD functions have been computed by carrying out single point energy calculations at the PB86/TZ2P level of theory on the B3LYP/6 – 31 + G(d,p) optimized geometries by employing ADF program package . Previous studies clearly showed that the CD function is marginally affected by the employed level of theory, so that we are confident that the present CD functions results at the PB86/TZ2P level are consistent with the B3LYP/6 – 31 + G(d,p) calculations. We also verified that the dispersion correction by Grimme (BP86‐D3) does not affect the charge density distribution.…”
Section: Methodssupporting
confidence: 70%
“…An adequate choice is the isodensity boundary, where the electron density of the noninteracting fragments become equal. The CD analysis was successfully employed in the description of both coordination bonds and weak secondary interactions, such as HB and XB …”
Section: Methodsmentioning
confidence: 99%
“…The relative electron-donating abilities of the phosphine by inductive effect of the alkyl groups from Me to tBu stabilized the electrostatic interaction of the Au-CO bond, ∆Eelect, from -110.1 to -115.5 kcal/mol ( Table 2, entries 1-5). However, in contrast to the protodeauration step study by Belanzoni and co-workers, 39 the electrostatic contribution is quenched by the destabilizing Pauli repulsion term, going from 148.0 and 137.2 kcal/mol for 1-tBu and 5-Me respectively, and spanning an energy range of 10.8 kcal/mol. The positive value of the "ionic" contribution (∆E 0 = ∆Eelect + ∆EPauli) from 27.1 to 32.8 kcal/mol for 1-Me and 4-Cy and respectively) indicates that the interaction between the gold cationic moiety and CO is destabilized due to steric repulsion (ΔEPauli) and corresponds approximately to one half of the covalent component (∆Eoi ≈ -66 kcal/mol).…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 59%